Evaluation of Analgesic Effect of Corn Silk Infusion (Zea mays L.) - Nidaan Khafiya; Andri Tilaqza; Reza Hakim (Nusantara Science and Technology Proceedings, 2023)
Corn silk (Zea mays L.) is a plant that is widely found in Indonesia but is still unexplored. In silico studies show that corn silk contains compounds that have the potential as analgesics by inhibiting the work of the enzyme cyclooxygenase (COX) which can reduce the production of prostaglandins by arachidonic acid, but these studies have not been proven in vivo. This study aims to evaluate the analgesic effect of corn silk infusion. Corn silk was extracted by the infundation method. A phytochemical screening test was conducted to determine the content of corn silk infusion. Analgesic effect was evaluated using analgesimeter rendal-selitto in 30 male wistar rats. The negative control group was given distilled water, the treatment groups were given 125, 250, and 500 mg/kgBW of corn silk infusion, and the positive control group was given mefenamic acid suspension of 45 mg/kgBW. Corn silk infusion contains flavonoid, saponin, and alkaloid compounds based on phytochemical screening tests. The administration of corn silk infusion with doses of 125, 250, and 500 mg/kgBW produced a percentage of pain inhibition at 13.2%, 13.89%, and 20.42% compared to mefenamic acid at 25.11%. The greater analgesic activity was observed by the maximum dose of the infusion (500 mg/kgBW). The effect of the infusion was also statistically significant (p<0.05) only in the maximum dose. The result obtained from this study shows that the Corn silk infusion contained phytochemical constituents with analgesic activities, therefore could be used in the management of pain conditions. Further research is needed regarding the toxicity test and its mechanism of action.